Strategi Inovatif Pengembangan Sumber Daya Manusia Dalam Industri Parawisata di Bangkalan - Shinta Nuria Salsabila; M Isa Anshori; Ahmad Kamil; Novia Jamilati (Pusat Riset dan Inovasi Nasional, 2024)
This research examines human resource development strategies in the tourism sector from the perspective of developing regional tourism potential. The existence of human resources is thought to play an important role in tourism development. Tourism human resources include tourists/tourists or as workers (employment). This research uses a qualitative approach, namely an inductive approach. This type of research is categorized as descriptive research. The research results show that the management, development and financing of tourist areas requires the support of many stakeholders (public, private and society) so that the process can run smoothly. The success of developing this area is also greatly influenced by conditions of security and political stability, the carrying capacity of human resources who have appropriate skills both in terms of quality and quantity.